Artificial Intelligence and the Rule of Law: Legal and Ethical Implications in Emerging Democracies - Jayadi, Irfan; Rais, Abdullah (Justicia Insight, 2025)
The rapid development of Artificial Intelligence (AI) presents significant challenges to the rule of law, particularly in emerging democracies. On one hand, AI offers opportunities to improve judicial efficiency, expand access to justice, and enhance transparency in legal governance. On the other hand, its implementation raises complex legal and ethical concerns, including algorithmic bias, threats to individual privacy, accountability of machine-based decisions, and risks to the principle of non-discrimination. This article examines the interplay between AI and the rule of law by highlighting normative challenges and ethical dilemmas that arise in the context of developing democratic systems. Employing a normative-legal approach combined with ethical analysis, this study emphasizes the need for adaptive, accountable, and human rights–based regulatory frameworks. The findings demonstrate that without adequate regulation, AI adoption may exacerbate legal and social inequalities. Conversely, when appropriately regulated, AI can serve as a strategic instrument to strengthen the foundations of the rule of law and support democratic consolidation.